Inverse emulsion-crosslinked cyclodextrin polymer nanoparticles for selective adsorption and chemiresistive sensing of BTEX. (June 2022) - Phillips, Bailey; Abani,; Lin, Hengyu; Wei, Peiran; Li, Chenxuan; Zhao, Mingzhen; Handy, Joseph; Banerjee, Sarbajit; Sue, Hung-Jue; Pentzer, Emily; Al-Hashimi, Mohammed; Zhou, Hong-Cai; et al.
Abstract: Macrocyclic molecules, such as cyclodextrins, possess selective host-guest binding properties and can be incorporated into larger architectures for adsorption or sensing applications. An inverse emulsion approach was developed for the synthesis of crosslinked polymer nanoparticles of cyclodextrins (CD-PNP) without the employment of any additional linker or spacer. The macrocyclic cavity of cyclodextrin endows CD-PNP with the ability to selectively bind benzene, toluene, ethylbenzene, and xylenes (BTEX) molecules according to their size and shape, while the cross-linked porous network enables high adsorption capacities (e.g. 378.1 mg/g for benzene). The solution processability of nanoparticles enables feasible incorporation of CD-PNP, together with carbon nanotubes (CNT), into composite chemiresistive sensor devices. These sensors exhibit high sensitivity and excellent selectivity in response to the exposure of various BTEX vapors. Highlights: Feasible inverse emulsion approach to synthesize nanoparticles of cross-linked cyclodextrin without any additional linker. High capacity and excellent selectivity in benzene adsorption. Prototype chemiresistive sensor device shows high sensitivity and excellent selectivity in response to various BTEX vapors.